Is my hand connected to my body? The impact of body continuity and arm alignment on the virtual hand illusion - Perez-Marcos, Daniel (Springer Netherlands, 2011)
When a rubber hand is placed on a table top in a plausible position as if part of a person’s body, and is stroked synchronously with the person’s corresponding hidden real hand, an illusion of ownership over the rubber hand can occur (Botvinick and Cohen 1998). A similar result has been found with respect to a virtual hand portrayed in a virtual environment, a virtual hand illusion (Slater et al. 2008). The conditions under which these illusions occur have been the subject of considerable study. Here we exploited the flexibility of virtual reality to examine four contributory factors: visuo-tactile synchrony while stroking the virtual and the real arms, body continuity, alignment between the real and virtual arms, and the distance between them. We carried out three experiments on a total of 32 participants where these factors were varied. The results show that the subjective illusion of ownership over the virtual arm and the time to evoke this illusion are highly dependent on synchronous visuo-tactile stimulation and on connectivity of the virtual arm with the rest of the virtual body. The alignment between the real and virtual arms and the distance between these were less important. It was found that proprioceptive drift was not a sensitive measure of the illusion, but was only related to the distance between the real and virtual arms. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11571-011-9178-5) contains supplementary material, which is available to authorized users.